PERKAWINAN ANTAR NEGARA DI INDONESIA BERDASARKAN HUKUM PERDATA INTERNASIONAL DAN HUKUM PERKAWINAN DI KOTA TANJUNGBALAI - Hutabarat, Dany Try Hutama; Tarigan, Elisa Br; Manurung, Agave; Tarigan, Nurma Anggita Putri; Samosir, Putri Humaiza; Sitorus, Herman; Fafaruq, Lintang Al; Azmi, Fahri; Poliansyah, Dimas; Zahra, Pelangi Aulia; Manalu, Fernaldo; Marpaung, Aldo Rizky Bahari; et al. (Nusantara Hasana Journal, 2022)
Marriage is a legal event if the marriage is a legal marriage. The rapid development of science and technology has an influence on the ease of relations between human beings, between ethnic groups, and between countries in all aspects of life. One of the effects is the occurrence of mixed marriages between spouses of different nationalities, including Indonesian workers and workers from other countries. Marriages of different nationalities often cause problems, especially with regard to the process of registering a marriage that will take place, whether in the country of origin of the prospective husband or in the country of origin of the prospective wife. The procedure for marriage between countries according to international civil law explains that the marriage rules for couples of different nationalities, returned to each partner will use the law of the country of the prospective husband, or use the law of the country of the prospective wife. Problems that arise in the procedure for mixed marriages of different nationalities are at the stage of preparing a certificate from the marriage registrar and at the stage of preparing letters or other documents. The solution to the problems that arise in the mixed marriage procedure that has been prepared by the government is to provide clear information and provide a website for couples who are getting married. Those who are naughty must be given strict sanctions.